Time-restricted feeding reduced blood pressure and improved cardiac structure and function by regulating both circulating and local renin-angiotensin systems in spontaneously hypertensive rat model - Xin Yi; Razif Abas; Raja Abdul Wafy Raja Muhammad Rooshdi; Jie Yan; Canzhang Liu; Chongshuang Yang; Teng Gao; Weijing Sun; Ummi Nadira Daut (PLoS ONE, 2025)
Objective To investigate whether time-restricted feeding (TRF) can reduce blood pressure (BP) and improve cardiac structure and function in spontaneously hypertensive rats (SHRs) by regulating the renin-angiotensin system (RAS). Methods Wistar Kyoto rats and SHR underwent 16 weeks of TRF intervention, with daily feeding restricted to 9 am–5 pm. The effects of TRF on systolic BP, diastolic BP, mean BP, body weight (BW), heart weight (HW), HW/BW ratio, cardiac structure and function, and RAS activity in the circulating and left ventricular (LV) tissues were investigated. Results TRF effectively reduced systolic BP, mean BP, diastolic BP, and BW; improved hypertension-induced cardiac structural and functional damage; and inhibited the ACE-Ang-II-AT1 axis in circulating and LV tissues. Conclusion TRF effectively inhibits RAS activity in both circulating and LV tissues, thereby lowering BP and mitigating structural and functional cardiac damage associated with hypertension.